Elevated and Correlated Expressions of miR-24, miR-30d, miR-146a, and SFRP-4 in Human Abdominal Adipose Tissue Play a Role in Adiposity and Insulin Resistance - Yury O. Nunez Lopez; Gabriella Garufi; Magdalena Pasarica; Attila A. Seyhan (International Journal of Endocrinology)
Objective. We explored the relationships among microRNAs (miRNAs) and SFRP4, as they relate to adipose tissue functions including lipolysis, glucose and glycerol turnover, and insulin sensitivity. Methods. Abdominal adipose tissue (AbdAT) levels of thirteen microRNAs (miRNAs), SFRP4, and VEGF in lean nondiabetic subjects (n=7), subjects with obesity (n=5), and subjects with obesity and type 2 diabetes (T2DM) (n=5) were measured by qPCR. Insulin sensitivity was measured by the euglycemic-hyperinsulinemic clamp. Osmium fixation and Coulter counting were used for adipocyte sizing. Data were analyzed using generalized linear models that adjusted for age, gender, and ethnicity. Results. AbdAT miR-24, miR-30d, and miR-146a were elevated in subjects with obesity (P<0.05) and T2DM (P<0.1) and positively correlated with measures of percent body fat by DXA (rmiR.24=0.894, rmiR.146a=0.883, P<0.05), and AbdAT SFRP4 (rmiR.30=0.93, rmiR.146a=0.88, P<0.05). These three miRNAs additionally correlated among themselves (rmiR.24~miR.146a=0.90, rmiR.30~miR.146a=0.85, P<0.01). Conclusions. This study suggests a novel association between the elevated levels of miRNAs miR-24, miR-30d, and miR-146a (apparently coregulated) and the level of SFRP4 transcript in AbdAT of subjects with obesity and T2DM. These molecules might be part of a regulatory loop involved in AbdAT remodeling/adiposity and systemic insulin resistance. This trial is registered with NCT00704197.